Implementasi Pembelajaran Matematika Berbasis Peta Konsep Pada Materi Lingkaran Ditinjau Dari Komunikasi Matematika Kelas VIII SMP Negeri 2 Banyudono - Ariyanti, Risa; , Dra.Nining Setyaningsih, M. Si (2017)
The purpose of this study to examine (1) the effect of the learning model Concept Map toward mathematics learning achievement of student, (2) the effect of mathematics communication toward mathematics learning achievement of student, (3) the interraction between the learning model dan mathematics communication toward mathematics learning achievement of student. This research was an experimental research with giving treatment learning model. This research type is quantitative research with a quasi-experimental design. Population dan sample SMP Negeri 2 Banyudono eight grade student. The sampling technique using cluster random sampling, in order to obtain class VIII F as the experimental and class VIII E as the control class. The data collection technique using the test metds, questionnaire dan documentation. Data were analyzed using analysis of variance of two paths with difference cell. The results of the study significant's level 5 % is (1) there is a significant influence of the learning model Concept Map toward mathematics learning achievement of student with Fa=4,24, (2) there is significant influece mathematics learning achievement of student with Fb=11,88, (3) there is no interraction between the learning model and mathematics toward communication mathematics learning achievement of student with Fab=1,19.